Site-specific peroxidation modulates lipid bilayer mechanics. (January 2021) - Chng, Choon-Peng; Sadovsky, Yoel; Hsia, K. Jimmy; Huang, Changjin
Abstract: Peroxidation of plasma membranes, characterized by oxidative attack of lipidic carbon–carbon double-bonds in unsaturated fatty acids, has been identified as an important biochemical event in multiple pathological conditions, including neurodegenerative diseases, atherosclerosis, diabetes, preeclampsia, aging, cancer, etc. Changes to the lipid bilayer structure as a result of lipid peroxidation may lead to lipid membrane malfunction, and consequently initiate further downstream biochemical cascades. However, how lipid peroxidation modulates the mechanical properties of lipid membranes remains largely controversial. In this study, we investigate the peroxidation of lipids with polyunsaturated fatty acid tails using molecular dynamics simulations. By systematically varying the oxidation site, we find that lipid peroxidation alters the biophysical properties of bilayer membrane in a peroxidation site-specific manner. Specifically, our results suggest that peroxidation at sites in the bilayer interior disturbs and softens the membrane, whereas peroxidation at sites near the membrane–water interface results in a more ordered and stiffer membrane. Such a peroxidation site-specific modulation of lipid membrane mechanics provides an explanation for the contradictory results obtained in previous experiments. Our study paves the way for an improved understanding of the initiation of the downstream cellular dysfunction caused by lipid peroxidation. Graphical abstract: